Mechanisms of brain overgrowth in autism spectrum disorder with macrocephaly - Currey, Laura; Harvey, Tracey; Pelenyi, Alexandra; Piper, Michael; Thor, Stefan (Frontiers in Neuroscience, 2025)
Autism spectrum disorder (ASD) is a highly prevalent human disorder with extensive clinical and genetic heterogeneity. One notable ASD subgroup that often manifest with more severe symptoms comprises individuals with an enlarged head (macrocephaly), often accompanied by an enlarged brain (megalencephaly). Here, we focus on the macrocephalic ASD subgroup and discuss the biological processes that may underlie brain overgrowth in individuals with ASD, including excess neurogenesis or gliogenesis, decreased cell death, neuronal hypertrophy, and elevated myelination. We also discuss the signaling and epigenetic pathways implicated in macrocephalic ASD. By examining the biological processes and the molecular pathways involved we seek to provide insight into the mechanisms underpinning macrocephalic ASD.